MEASURING THE RELATIONSHIP BETWEEN KNOWLEDGE MANAGEMENT, ORGANIZATIONAL LEARNING, AND INNOVATION: A STUDY OF JAMMU & KASHMIR TOURISM DEVELOPMENT CORPORATION, INDIA - Singh, Ramjit; Tantray, Zahid (ENLIGHTENING TOURISM. A PATHMAKING JOURNAL, 2022)
The present research focuses on the impact of Knowledge Management and Organizational Learning on Innovation in tourism organization. This study works on a model with Knowledge Management and Organizational Learning as inputs to promote Innovation. The study has used the descriptive research method, for which the data were collected through a questionnaire from 101 employees of Jammu and Kashmir Tourism Development Corporation (JKTDC) by adopting a census approach. Further regression analysis was applied to find the cause and effect relationship between Knowledge Management, Organizational Learning, and Innovation. Overall the study found that Knowledge Management has no significant effect on Innovation in the organization. While Organizational Learning significantly affects Innovation. It was also found that there is a significant difference in practicing Knowledge Management, Organizational Learning, and Innovation between levels of management. No significant difference was found regarding practicing Knowledge Management, Organizational Learning, and Innovation based on gender in the organization.